An Investigation on the Relation between Traditional Banking and Peer-to-Peer Lending from a Management Perspective - KUMARI, Sarasanabelli Prasanna; MOHANTY, Madhusmita (Theoretical and Practical Research in Economic Fields, 2024)
This research explores how P2P lending in India has impacted traditional banking. The leading influence of traditional banks has been threatened by P2P lending, a disruptive phenomenon of the lending business. In P2P financing, lenders and borrowers are linked directly together, with no need for institutions to stand as intermediaries. This method has numerous advantages, among them lower operating costs, fast approval of loans and increased access to banking services for the underprivileged. Our research was aimed at India's potential for peer-to-peer lending to disrupt existing banks or form a new market. This research not only introduces problems encountered by banks in consumer finance management, it also recognizes that these problems cannot be fully blamed on P2P lending technologies in any event. The results contribute to ongoing concerns over the dynamic interactions between traditional banking and peer-to-peer lending in emerging nations. The findings suggest a need for further research to determine the long-term impacts of these interactions on financial stability. This is crucial for policymakers and financial institutions to make informed decisions.